Nine new species of genus Homoneura from Qinling mountains in China (Diptera: Lauxaniidae) - Gao, Xuefeng; Shi, Li (Zootaxa, 2019)
Nine species from Qinling Mountains in China are described as new to science: Homoneura (Homoneura) anadaequata sp. nov., Homoneura (H.) bicolorata sp. nov., Homoneura (H.) dagupingensis sp. nov., Homoneura (H.) longiacutata sp. nov., Homoneura (H.) longicurva sp. nov., Homoneura (H.) miaoae sp. nov., Homoneura (H.) platimarginata sp. nov., Homoneura (H.) similicurvata sp. nov. and Homoneura (H.) spectabilis sp. nov. from Homoneura (H.) henanensis group. Keys to separate known species from new species are presented.